1977
DOI: 10.1128/jvi.22.1.194-202.1977
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage conversion of spore-negative mutants to spore-positive in Bacillus pumilus

Abstract: A pseudolysogenic phage, PMB1, was isolated from soil on the basis of its ability to increase the sporulation frequency of the oligosporogenic Bacillus pumilus strain NRS 576 (sporulation frequency, <1%). Several spore-negative mutants (sporulation frequency, <10-8) derived from strain NRS 576, which were converted to spore positive by infection with PMB1, were subsequently identified. PMB1 repeatedly grown on a given spore-negative mutant (e.g., GW2) converted GW2 cells to spore positive. Each plaque-forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Bacteriophage 4OW-14 DNA contains equimolar quantities of dTMP and the deoxynucleotide of a-putrescinylthymine (16), both of which are derived by postreplicational modification of a common precursor that is probably HMdUMP (22, 26). PMB1 is a "spore converting" phage for Bacillus pumilis (6). Mature PMB1 DNA has the same nucleotide composition as SP10 DNA, but the DNAs show little sequence homology (H. Witmer, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage 4OW-14 DNA contains equimolar quantities of dTMP and the deoxynucleotide of a-putrescinylthymine (16), both of which are derived by postreplicational modification of a common precursor that is probably HMdUMP (22, 26). PMB1 is a "spore converting" phage for Bacillus pumilis (6). Mature PMB1 DNA has the same nucleotide composition as SP10 DNA, but the DNAs show little sequence homology (H. Witmer, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The present work suggests that the existence of prophage may be closely related to the oligosporogenic phenotype of the parent strain of C. botulinum type A. However, Bramucci et al found that the one of the phages, PMB1, converted certain sporenegative mutants of B. pumilus to spore positive mutants (1), and the other phage, PMB12, complemented the sporulation defect in RNA polymerase mutants of Bacillus subtilis (2). Thus, the relationship between sporogenicity and the existence of plasmid or prophage has not yet been generally determined.…”
Section: Presence Of Bacteriophages In Mitomycin C-induced Culturesmentioning
confidence: 57%
“…A variation in the Oantigens of Salmonellae [ 16], the colony morphology in Streptococcus equi [17], toxin production in Co-rynebacterium diphtheriae [ 18,19 ], Clostridium botulinum [20] and Vibrio cholerae [21 ], phospholipase A production in B. cereus [22], thymidylate synthetase activity in a thymine deficient mutant of B. subtilis [23] and sporulation in spore-negative strains of8. pumilus [24] are all directed by prophages. As approximately half of the strains tested in this study were lysogenic, we considered whether this property had any survival value.…”
Section: Discussionmentioning
confidence: 99%